Humanity or sovereignty: a political roadmap for the 21st century - Storey, Lyndon (New York, 2006)
Despite the talk of globalization, current political discourse remains firmly anchored in the (S0(Bage of nationalism(S1 (Bwith concepts such as the national interest, national security, and gross national product (GNP) still defining the political agenda. This thought-provoking book challenges the hegemony of political nationalism, arguing that it is a false ideology that blinds us to the need for global political reform. This book proposes a new paradigm of (S0(Bhuman political justice(S1 (Bto replace the current (S0(Bjustice in one country(S1 (Bapproach. It forcefully reminds us that our human identity is more important than our national or religious identity and opens the campaign for a new (S0(BHuman Union(S1 (Bto progressively replace the nation-state as the primary focus of political activity.s
Keywords: International relations